1999
DOI: 10.3171/jns.1999.90.2.0315
|View full text |Cite
|
Sign up to set email alerts
|

Variables affecting convection-enhanced delivery to the striatum: a systematic examination of rate of infusion, cannula size, infusate concentration, and tissue—cannula sealing time

Abstract: Rate of infusion and cannula size can significantly affect convective distribution of molecules, whereas preinfusion sealing time and variations in infusate concentration have no effect in this small animal model. Understanding the parameters that influence convective delivery within the CNS can be used to enhance delivery of potentially therapeutic agents in an experimental setting and to indicate the variables that will need to be considered for optimum use of this approach for drug delivery in the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
202
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(213 citation statements)
references
References 16 publications
10
202
1
Order By: Relevance
“…These devices can lead to reflux, or backflow, along the outside of the catheter and unpredictable drug distributions [39]. The amount of reflux decreases as the diameter of the device is made smaller [29,7]. In a previous study we showed that a microfabricated device with cross-sectional area of 100 μm × 100 μm mitigates backflow at relatively high flow rates [31].…”
Section: Discussionmentioning
confidence: 99%
“…These devices can lead to reflux, or backflow, along the outside of the catheter and unpredictable drug distributions [39]. The amount of reflux decreases as the diameter of the device is made smaller [29,7]. In a previous study we showed that a microfabricated device with cross-sectional area of 100 μm × 100 μm mitigates backflow at relatively high flow rates [31].…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuation in this V d :V i linearity correlate with failure of infusate distribution as demonstrated previously by us in NHPs (Varenika et al, 2008) and in a clinical brainstem infusion case, where nonlinearity was caused by leakage into the surrounding ventricular space . Along with infusate leakage , other factors such as infusion rate and cannula size have been shown to affect the efficacy of CED (Chen et al, 1999). It should also be noted that V d :V i ratios are also affected by the composition of various anatomical regions, perhaps dependent on whether these regions are structurally composed of mainly gray or white matter (Szerlip et al, 2007).…”
Section: Aguilar Salegio Et Almentioning
confidence: 99%
“…31 Furthermore, CED within the defined infusion measurements does not produce cerebral edema or measurable increases in intracranial pressure. 32 For CED, one or more catheters are generally stereotactically implanted through a burr hole into or adjacent to either the enhancing portion of a tumor and/or the nonenhancing infiltrative surrounding tissue. A pressuredriven flow of the drug is achieved via an infusion pump, and the agent is directly infused into the target tissue at a predetermined concentration, rate, and duration.…”
Section: Convection-enhanced Deliverymentioning
confidence: 99%